The Development and Early Experience of a Destination Center of Excellence Program for Total Joint Arthroplasty. (January 2023) - Pelkowski, Jessica N.; Wilke, Benjamin K.; Glabach, Michelle R.; Bowman, Jacki C.; Ortiguera, Cedric J.; Blasser, Kurt E.; Crowe, Matthew M.; Sherman, Courtney E.; Ledford, Cameron K.
Abstract : High-volume total joint arthroplasty centers are becoming designated as destination centers of excellence to ensure quality of care while containing costs. This study aimed to evaluate the surgical patient journey through a new destination center of excellence program, review acute perioperative course trajectories, and report clinical outcomes. Our institution developed and implemented a destination center of excellence program to integrate into the existing total joint arthroplasty practice. A retrospective record review and analysis were performed for the first 100 destination center of excellence total knee arthroplasties and total hip arthroplasties enrolled in the program to evaluate program efficacy at a minimum 1-year follow-up. The study initially screened 213 patients, of whom 100 (47%) met program criteria and completed surgery (67 total knee arthroplasties and 33 total hip arthroplasties). The complication rate was 2%, and five patients (7.5%) required manipulation under anesthesia for stiffness after total knee arthroplasty. Two reoperations were needed: a neurectomy after total knee arthroplasty and a revision after total hip arthroplasty. The early experience of a destination center of excellence program has been favorable, with low complication rates and excellent outcomes.